Development of acid-base chemistry student activity sheet to improve metacognitive skills in Senior High School - Almira Nindya Divamita; Utiya Azizah (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
This study aimed to determine the feasibility of STUDENT ACTIVITY SHEET SAS to improve students' metacognitive skills on the acid-base subject. The research used a 4-D development model. Data were collected through interviews, questionnaires, observation, and written tests. The research subjects were 36 students in class eleventh Science at the 5 Senior High School Madiun, East Java, Indonesia. The study used one pre-test and post-test control group design. Results showed that: 1) The average percentage of validity is 87%, which is categorized as very valid 2) The average percentage of practicality, which includes the results of student response questionnaires and student activity observations, is 94% and 100%, respectively, which both of them are categorized as very good; and 3) The n-gain of effectivity, which includes the results of the pre-test-post-test cognitive and metacognitive skills are 0.57 and 0.62, respectively. The inventory questionnaire resulted in a value of 94%, which is categorized as very good, and the observation of metacognitive skills resulted in 100% with very good criteria.